2013 Ocean Electronics (SYMPOL) 2013
DOI: 10.1109/sympol.2013.6701929
|View full text |Cite
|
Sign up to set email alerts
|

Design of optimal power source for NIOT offshore moored buoy system

Abstract: The moore cyclone and Tsunami w data from these moore power system attained system.Non-rechargeab because the buoy sys prone to damage. Late battery would power battery can take over. buoy system to cater th Index Terms-Battery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The Integrated Marine Surveillance System (IMSS) implemented in the Indian moored buoy programme is the first of its kind, using an approach that provides real-time meteorological and oceanographic data via 3G telemetry and/or general packet radio service (GPRS; Venkatesan 2014). An uninterrupted power source is required to run all the sensors working at sea, which are unattended for long periods; with this in mind, NIOT developed wind-powered buoys (Kesavakumar et al 2013). To study Polar-Indian monsoon teleconnections, a multi-sensor moored observatory was deployed in the Arctic region (PIB GoI 2014).…”
Section: New Technologies Challenges and Limitationsmentioning
confidence: 99%
“…The Integrated Marine Surveillance System (IMSS) implemented in the Indian moored buoy programme is the first of its kind, using an approach that provides real-time meteorological and oceanographic data via 3G telemetry and/or general packet radio service (GPRS; Venkatesan 2014). An uninterrupted power source is required to run all the sensors working at sea, which are unattended for long periods; with this in mind, NIOT developed wind-powered buoys (Kesavakumar et al 2013). To study Polar-Indian monsoon teleconnections, a multi-sensor moored observatory was deployed in the Arctic region (PIB GoI 2014).…”
Section: New Technologies Challenges and Limitationsmentioning
confidence: 99%
“…This controlled charging mechanism helps in reducing hydrogen gas generation due to overcharging and thus sustaining the useful life and hence the reliability of the battery. The architecture and the performance of the system reported (Kesavakumar et al, 2013) is shown in Figure 5.…”
Section: Generation I: Lead Acid Chemistrymentioning
confidence: 99%
“…The hybrid power system is realized using solar charged powered lead acid batteries used in Generation I and backed by primary LiSoCl 2 battery storage (Kesavakumar et al, 2013) as in Generation II. The architecture is being implemented in the MSB.…”
Section: Generation Iii: Cost-optimized Reliable Hybrid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the SWB is relatively recently developed compared to LIB, those data-based SOH estimation works for the SWB are rarely reported. Lastly, under marine environments, the buoy needs to be self-powered with harvesting devices such as PV [34], wind [35] and wave harvester [36] for longlasting system operation. Also, intelligent power management techniques are required, since the buoy lightening causes large power consumption.…”
Section: Introductionmentioning
confidence: 99%